A VAR Based Study on Energy Consumption and Economic Growth - Alshami, Mohamed (International Journal of Energy Economics and Policy, 2023)
Economic growth and energy consumption are interrelated for an economy and these variables are expected to indicate a positive correlation. This relationship has been probed in the study in the context of the United Arab Emirates for the time period 1996-2020. The study uses basic regression and Vector Auto Regression techniques for analysis. The study found that energy consumption and non-renewable energy consumption are positively correlated, are dependent on the country’s economic growth and this relationship is optimum at a lag of 7 years.